E-waste forensics: An overview - Neeti Kapoor (Elsevier, 2021)
E-waste or electronic waste is simply the discarded or not in use electronic or electrical gadgets or their parts. Increased use of electronics in the modern era has led to a huge increase in e-waste produced by each passing hour of the day. The growing e-waste is not out of the list in providing opportunities for criminals to carry out their illegal activities that has surged worldwide. Crimes related to e-waste includes a range of illegal trades in e-waste, environmental crimes and cyber-crimes. Even after the “deletion” or “formatting” of the storage media, the data is still present and can be retrieved and used for ulterior motives by cybercriminals. This article outlines the forensic aspects of e-waste termed as e-waste forensics, including the significant impacts of e-waste, e-waste and crimes and some preventive measures.